Financial liberalization, bank crises and growth: Assessing the links - Alessandra Bonfiglioli; Caterina Mendicino (Stockholm School of Economics, The Economic Research Institute (EFI), 2004)
This paper studies the effects of financial liberalization and banking crises on growth. It shows that financial liberalization spurs on average economic growth. Banking crises are harmful for growth, but to a lesser extent in countries with open financial systems and good institutions. The positive effect of financial liberalization is robust to different definitions. While the removal of capital account restrictions is effective by increasing financial depth, equity market liberalization affects growth directly. The empirical analysis is performed through GMM dynamic panel data estimations on a panel of 90 countries observed in the period 1975-1999.
Keywords: C23; F02; G15; O11; 330; Capital account liberalization; equity market liberalization; financial development; institutions; dynamic panel data; ARCH-Modell; Kapitalmarktliberalisierung; Bankenkrise; Wirtschaftswachstum; Schätzung